Learning styles and attitudes towards Mathematics in students at POLISAL, UNAN-Managua (Revista Torreón Universitario, 2020)
The purpose of this research has been the analysis of the relationship between learning styles and attitudes towards Mathematics in students at the Polytechnic Institute of Health (POLISAL), UNAN-Managua. The study was descriptive-correlational, with a population of 427 students of the first years of the Majors offered by POLISAL and a sample of 203 distributed proportionally by shift and major. The simplified CHAEA questionnaire and the attitude scale towards Mathematics were applied to each participant. The results indicate that the predominant style in the sample is reflective and, in general, the attitude toward Mathematics is favorable. In addition, the non-parametric chi-square method shows that there is no relationship between the study variables, that is, a student's learning style has no effect on his attitude towards Mathematics.
Keywords: learning styles; attitude towards mathematics; POLISAL